2019
DOI: 10.3390/cli7060074
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Climate Change Mitigation and Adaptation Action: A Household Study in the Nuevo Leon Region, Mexico

Abstract: Household-level mitigation and adaptation actions are important because households make a significant contribution to greenhouse gas emissions and are severely affected by climate change. However, there is still very little understanding of the factors that influence household-level mitigation and adaptation action. From a review of literature, we identified the factors that potentially influence climate mitigation and adaptation actions of households, which we then tested using survey data from 622 households… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…The study by Hung and Bayrak [92] found that interdependency of husbands and wives' motivations for behavioral change to climate change mitigation also plays an important role in climate change mitigation behavior of the household. Perceived knowledge and financial self-efficacy as well as other behavioral factors were found as having significant influence on households' climate change mitigation behavior in Mexican households [93,94]. The study by Nauges and Wheeler [95] revealed that climate change concerns of households positively influence specific mitigation actions, but mitigation behavior may negatively affect households' climate change concerns as well.…”
Section: Discussion Of Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The study by Hung and Bayrak [92] found that interdependency of husbands and wives' motivations for behavioral change to climate change mitigation also plays an important role in climate change mitigation behavior of the household. Perceived knowledge and financial self-efficacy as well as other behavioral factors were found as having significant influence on households' climate change mitigation behavior in Mexican households [93,94]. The study by Nauges and Wheeler [95] revealed that climate change concerns of households positively influence specific mitigation actions, but mitigation behavior may negatively affect households' climate change concerns as well.…”
Section: Discussion Of Resultsmentioning
confidence: 96%
“…Especially in dealing with renewables [89] and energy efficiency [90] barriers in households. Recent studies [91][92][93][94][95] on climate mitigation behaviors identified the other non-economic drivers of climate change mitigation behavior are much more important but not properly addressed in shaping policies. Awareness, personal, and social norms were found to be equally important as monetary factors [91].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…For the purpose of identifying barriers, amongst the 30 or so questions in the questionnaire, an open-ended question was asked: What are the barriers to climate change action in your household? It is the results of the analysis of this question that forms the basis of this paper, while the results of other questions are addressed in another paper [46]. Ethics approval was given for the research by the Faculty of Spatial Sciences at the University of Groningen, and all principles of ethical research, specifically informed consent, were observed [47].…”
Section: Methods and Background To The Study Regionmentioning
confidence: 99%
“…In order to become aware of climate change, it is important to perceive that climate change presents a problem for the sustainability of our planet. Understanding the risks and the impacts derived from climate change is key to perceive the need to deal with it [8,[52][53][54][55][56][57]. Furthermore, awareness is materialized in the willingness to act and participate in taking measurements to face the challenges posed by climate change [8,48,52,[54][55][56][57][58][59][60].…”
Section: City Resilience and Stakeholders' Awareness Of Climate Changementioning
confidence: 99%
“…Understanding the risks and the impacts derived from climate change is key to perceive the need to deal with it [8,[52][53][54][55][56][57]. Furthermore, awareness is materialized in the willingness to act and participate in taking measurements to face the challenges posed by climate change [8,48,52,[54][55][56][57][58][59][60]. This participation depends on the commitment level, the higher the commitment level the better the quality and efficiency of the implemented efforts to deal with climate change [48,[57][58][59][60][61].…”
Section: City Resilience and Stakeholders' Awareness Of Climate Changementioning
confidence: 99%